Framing femicide : critical discourse analysis of the Sunday Times and Sowetan print media newspapers - Mphahlele, Kgothatso Shaun (My University, 2025)
Introduction – Framing Femicide is an intervention through the convergence of politics and the media. This study set out to critically analyse how print media ‘frames’ femicide as a social phenomenon by placing at the centre of critique, politically influenced factors such as language and ownership of the media as the “fourth estate” and exploring how these two factors factor in how the framing of the death (read as femicide) of black womxn is undertaken in selected newspaper houses in South Africa. This study used Critical Discourse Analysis (CDA) and agenda setting theory both independently and simultaneously, as theoretical underpinnings. The study explored how language, central to doing critical inquiries, was employed by print media to frame femicide. Methodology - The study adopted a Qualitative Research outlook deemed “particularly good at examining and developing theories that deal with the role of meanings and interpretations” to conduct what Saidiya Hartman calls “a mode of close narration” by analyzing newspapers as documents. The study sampled the work of Fairclough (1992, 2012, 2013), Wodak (2014), and van Dijk (2015) to craft ways through which CDA can employed as part of a critical social analysis to interrogate the framing and representing femicide in selected print media houses. Motivation - The rationale of the study lay in the fact of numbers, which ranked South Africa among the highest nation states where femicide prevails. Scholarship reveals that a woman is murdered every 4 (four) hours, and 57 1% of those murders are done by intimate partners. Owing to this, South Africa’s femicide rate is arguably 5 times higher than the global rate. This warrants an interrogation on how the “fourth estate” as a critical tool in a society is a constituent element which reflects the social realities and power dynamics when framing femicide. Results – The study found that journalists in their framing of femicide conflate terms that relate to generalized gender-based violence which all-inclusive terms, which by default are not limited to women and specifically to violence against women. Recommendations – The study recommends that writers, authors, and journalists engaged in news production for print media take caution of the implications of writing about social phenomena and not conflating common terms deployed in framing particular discourses.
Thesis (M. A. (Political Science)) -- University of Limpopo, 2025
Keywords: Femicide; Critical discourse analysis; Framing; Newspapers; South Africa; Women -- Crime against; Critical discourse analysis; Frames (Sociology); Newspapers